Analisis Prestasi Akademik, Pengalaman Magang, Kompetensi dan Motivasi Kerja terhadap Kesiapan Kerja Mahasiswa Universitas Gunadarma - Ainunisa Ainunisa; Mohammad Abdul Mukhyi (PPIMAN Pusat Publikasi Ilmu Manajemen, 2025)
In the ever-evolving business landscape, student work readiness plays a vital role as a foundation for successful entry into the workforce. This study aims to examine the factors influencing student work readiness by analyzing the effects of academic achievement, internship experience, competence, and work motivation among management students at Gunadarma University Kalimalang. The research employs a quantitative approach using primary data collected through questionnaires distributed to 250 respondents. Data were analyzed using SmartPLS 4.0 with various statistical tests, including convergent validity, discriminant validity, Average Variance Extracted (AVE), R-Square, predictive relevance (Q²), and path coefficient analysis. The findings reveal that academic achievement and work motivation significantly and positively affect students’ work readiness, indicating that strong academic performance and high motivation enhance preparedness for entering the workforce. Conversely, internship experience and competence do not have a significant impact on students’ work readiness, suggesting that practical experience and skill development may not be fully integrated into the academic process. This study underscores the importance of fostering motivation and maintaining academic excellence to improve graduate employability and readiness in a competitive job market.